Tyskland under hakkorset
Continued by: Fascism (ZK 53404). - German ed.: Hakenkreuz über Deutschland (ZK 16067). - French ed.: Sous la croix gammée (ZK 53399). - Eng. ed.: Germany under the swastika (ZK 53401). - Spanish ed.: Bajo la esvástica (ZK 53402).